Reasons for production and reasons for the environment: the introduction of the extra-penal parameter “best available technique” in the origins of the cautionary obligations system - Claudia Palmeri (Lexambiente, 2019)
Today, the European system of setting out the inspiring principles for political action in environmental matters legitimates the adoption of restrictive measures founded on the principle of precaution. In this present work we investigate the possibility of considering such cautionary obligations in a prudent manner in the light of the fundamental principle of guilt (nulla poena sine culpa) sanctioned by art. 27 Cost.